EXTENDING THE RANGE OF DETECTION OF AERODROME BEAM SIGNALS IN ADVERSE METEOROLOGICAL CONDITIONS - Golovenskyy, Volodymyr (Proceedings of National Aviation University (archive), 2018)
Goal: Successful and safe landing of the aircraft at night in adverse meteorological conditions is possible subject to the complex use of radar, satellite radio navigation systems and lighting devices, with lighting equipment being of particular importance at the end of the flight, since they provide the necessary visualization of the runway. One of the most effective methods of increasing the safety of flights is the creation of an additional independent optical transmission channel between the aircraft and the runway. As such a channel may be a system for observing aerodrome radiation signals from the aircraft in adverse meteorological conditions using the infrared (IR) radiation spectrum. The aim of the work is carrying-out of theoretical analysis of the possibilities of increasing the range of detection of beam aerodrome signals in order to increase the accuracy and reliability of the aircraft landing approach due to the use of medium and longwave infrared radiation ranges for reception of navigation information. Method: we made the mathematical estimation of the dependence of the range of detection of the spot beam signals on the wavelength and source power. Results: Such dependences are designed for infrared wavelengths of 0.554 μm, 1.0 μm, 4.0 μm, 10 μm, which coincide with the atmospheric transparency windows in different conditions of distribution: transparent atmosphere, haze, fog. It has been shown analytically that using infrared monochromatic emitters and frequency coherent photodetectors with a high specific detection capability, it is possible to significantly increase the detection range of beam signaling targets compared with the shorter wavelengths of the visible range, both in the conditions of a transparent atmosphere and in the presence of a water-aerosol medium. Mathematical relations for comparative estimation of the range of the source-receiver system with different working wavelengths are obtained. Numerical graphical analysis shows that at the same power sources of radiation, the range of detection of infrared beam signals occurs at significantly longer distances compared with light signals of the visible range. Discussion: The use of the light signal monitoring system for following up the aircraft when landing in adverse meteorological conditions, which developed using the above mentioned principles, will allow the aircraft crew to observe landing infrared lights on the monitor screen at a considerable distance in adverse weather conditions and to make the necessary adjustments when deviating of the aircraft from the glide, which will significantly increase flight safety and reduce the negative psychological stress on the aircraft crew at the most difficult and responsible phases of the flight.